Negative impacts of European General Personal Data Protection Regulation (GDPR) and Personal Data Protection Act B.E. 2562 on stakeholders - Thograweewong, Kanathip (Rajapark Journal, 2021)
The research aimed to study 1) Negative impact in several aspects caused by the principles, elements, and conditions of European General Personal Data Protection Regulation (GDPR) 2) Negative impact in several aspects caused by the principles, elements, and conditions of Thailand’s Personal Data Protection Act B.E. 2562 by comparative analysis with GDPR 3) proposal to reduce the negative impact. The methodology of this research is qualitative research by conducting content analysis and comparative analysis of Thai and European Union law. The research results were found as follows On the one hand, The General Data Protection Regulation (GDPR) of the European Union has provisions to protect the personal data of people such as requiring business sectors who are deemed as “data controller” to provide a measure for protecting personal data and granting several rights to the data subject. On the other hand, this law causes a negative impact in several dimensions for various stakeholders such as causing unfair trade competition, the prohibitive cost of compliance for small and medium business, limiting certain human rights especially freedom of speech, providing an opportunity for abuses and cybercrimes. As for Thailand, “The Personal Data Protection Act” has been enacted and take effect in May B.E. 2563. The comparative analysis indicates that this Act has similar content and element to GDPR. Consequently, the research indicates the tendency of negative impacts from this law as those caused by GDPR.